Hair cortisol, cortisone and DHEA concentrations and the composition of microbiota in toddlers - Koskinen Maarit K; Aatsinki Anna; Kortesluoma Susanna; Mustonen Paula; Munukka Eveliina; Lukkarinen Minna; Perasto Laura; Keskitalo Anniina; Karlsson Hasse; Karlsson Laura (United Kingdom, 2025)
Animal research suggests that the gut microbiota and the HPA axis communicate in a bidirectional manner. However, human data, especially on early childhood, remain limited. In this exploratory design, we investigated the connections between long-term HPA axis functioning, measured as cortisol, cortisone or dehydroepiandrosterone concentrations and their ratios from hair segments of three centimeters, and gut microbiota profiles, (measured as diversity and bacterial composition by 16 S rRNA sequencing) in healthy 2.5-year-old toddlers (n = 135) recruited from the FinnBrain Birth Cohort Study. The alpha diversity of the microbiota was studied by linear regression. Beta diversity analyses with weighted UniFrac or Bray-Curtis distances were performed using PERMANOVA. The bacterial core genus level analyses were conducted using DESeq2 and ALDEx2. These analyses suggested that hair sample concentrations of separate hormones, cortisol/cortisone and cortisol/dehydroepiandrosterone ratios were associated with various gut bacterial genera such as the Veillonella, the [Ruminococcus] torques group and [Eubacterium] hallii group, although multiple testing correction attenuated the p-values. Alpha or beta diversity was not linked with either steroid concentrations or ratios. These findings in toddlers suggest that long-term HPA axis activity may be related to genera abundancies but not to ecosystem-level measures in gut microbiota. The influence of these observed interrelations on later child health and development warrants further research.